Sternoclavicular septic arthritis due to methicillin-resistant Staphylococcus aureus in a patient with a suprapubic catheter. (18th February 2015) - Monteiro, Nadine; Moleiro, Filipa; Lérias, Graça; Silva, Alberto Mello
Abstract : We report a case of a 74-year-old man who presented to the emergency department with a 1-week history of fever. He had a meatal stenosis and had a suprapubic catheter for 10 months, and had a recent hospitalisation for urosepsis with bacteraemia due to methicillin-resistant Staphylococcus aureus after manipulation of the catheter. Clinical examinations were performed in the emergency department and the patient was hospitalised with the diagnosis of recurrent urinary tract infection. The following day, we noticed the development of a mass in the left sternoclavicular joint with inflammatory signs and excruciating pain. Ultrasonographic findings led to the diagnosis of left sternoclavicular synovitis, and methicillin-resistant S. aureus grew in blood cultures leading to the diagnosis of sternoclavicular septic arthritis. Treatment with vancomycin and gentamicin was started and maintained for 4 weeks with complete resolution of symptoms and no complications or sequelae.